Reproductive male partner testing when the female is identified to be a genetic disease carrier. (24th September 2020) - Simone, Laurie; Khan, Shama; Ciarlariello, Molly; Lin, Julia; Trackman, Sarah; Heiman, Gary A.; Ashkinadze, Elena
Abstract: Objective: To quantify carrier testing uptake rates for male partners of women found to be a carrier(s) for autosomal recessive conditions and to understand reasons for declining testing (uptake rate). Methods: A retrospective chart review of 513 female patients seen at Rutgers‐Robert Wood Johnson Medical School found to be carriers through expanded carrier screening (ECS) panels. The aims of this study were to determine how often their male partner chose testing, reasons for declining and the type of methodology chosen for their screening. Results: Male partner uptake rate was 77%. We identified that the most significant barrier to male partner testing is female patients not following up on their own carrier screening results, thus missing the opportunity for partner testing. When male partners were provided options for testing, the most reported reason for declining is the belief it would have no impact on pregnancy management (20%). A carrier couple rate of 8.3% was identified of partners tested. Conclusion: Despite a relatively high male testing uptake rate, a quarter of carrier females did not proceed with testing their partner. To ascertain fetal risk, results for both parents is necessary. Pretest counseling should stress need for potential male partner follow‐up testing.